Reduction of the incidence of pressure sores by an education program on nursing care. - Srisupan V. (2014)
OBJECTIVES: To determine whether an education and campaign program would reduce the incidence of pressure sores. MATERIAL AND METHOD: The study was performed in a 1,400-bed teaching hospital in Thailand with a total number of 697patients from 47 wards for a point prevalence study; 1,201 and 1,268 patients from 12 wards to determine whether reduction of pressure sore occurrence would be obtained by an education program. RESULTS: The point prevalence of pressure sores was 10.8%. The significant risk factors were age older than 60 years, fecal incontinence, and history of diarrhea. The occurrence of pressure sores was significantly reduced after the educational program from 9.91% to 5. 76%. The education on patient care aiming at reduction of the occurrence of pressure sores could be adopted nation-wide in order to reduce the morbidity, mortality and expenses. CONCLUSION: The education program was effective in reducing the incidence of pressure sores.